A CD25− Positive Population of Activated B1 Cells Expresses LIFR and Responds to LIF - Tumang, Joseph R.; Holodick, Nichol E.; Vizconde, Teresa C.; Kaku, Hiroaki; Frances, Ruben; Rothstein, Thomas L. (Frontiers in Immunology, 2011)
B1 B cells defend against infectious microorganisms by spontaneous secretion of broadly reactive “natural” immunoglobulin that appears in the absence of immunization. Among many distinguishing characteristics, B1 B cells display evidence of activation that includes phosphorylated STAT3. In order to identify the origin of pSTAT3 we examined interleukin-2 receptor (IL-2R) expression on B1 cells. We found that some (about 1/4) B1a cells express the IL-2R alpha chain, CD25. Although lacking CD122 and unresponsive to IL-2, B1a cells marked by CD25 express increased levels of activated signaling intermediates, interruption of which results in diminished CD25. Further, CD25+ B1a cells contain most of the pSTAT3 found in the B1a population as a whole. Moreover, CD25+ B1a cells express leukemia inhibitory factor receptor (LIFR), and respond to LIF by upregulating pSTAT3. Together, these results define a new subset of B1a cells that is marked by activation-dependent CD25 expression, expresses substantial amounts of activated STAT3, and contains a functional LIF receptor.